Creativity and Community among Autism-Spectrum Youth Creating Positive Social Updrafts through Play and Performance - Smagorinsky, Peter (Palgrave Studies In Play, Performance, Learning, and Development, 2016)
This edited volume explores the roles of socially-channeled play and performance in the developmental trajectories of young people who fall on the autism spectrum. The contributors offer possibilities for channels of activity through which youth on the autism spectrum may find acceptance, affirmation, and kinship with others. "Positive social updraft" characterizes the social channels through which people of difference might be swept up into broader cultural currents such that they feel valued, appreciated, and empowered. A social updraft provides cultural meditational means that include people in a current headed "upward," allowing people of atypical makeups to become fully involved in significant cultural activity that brings them a feeling of social belonging.